Direct electric current utilization in destruction of extremely halophilic bacteria in salt that is used in brine curing of hides - BİRBİR, MERAL; BİRBİR, YAŞAR (ELSEVIER, 2008)
Hydrolytic enzymes, which are produced by extremely halophilic bacteria in salt, may cause serious damage on salted hides and may result in significant economic losses. Therefore, to prevent halobacterial damage on hides, the antibacterial effects of different levels of direct electric current on extremely halophilic bacteria found in salt were examined in brine solution containing 20% NaCl and salt samples, liquid Brown media containing 20% NaCl, organic substances and salt samples, liquid Brown media separately inoculated with lipase, and protease producing extremely halophilic strains. Direct electric current (0.1 A, 0.2 A. 0.3 A and 0.4 A) inactivated extremely halophilic bacteria in salt, which was dissolved in the brine solution within 15 min, 10 min, 5 min and 3 min, respectively. Although 0.5 A direct electric current inactivated extremely halophilic bacteria in the salt samples (10(4)-10(5) CFU/g), which were dissolved in the brine solution within 1 min but treatment with 0.5 A direct electric current for 15 min was necessary to inactivate the extremely halophilic bacterial population in the salt samples dissolved in the liquid Brown media. Also, 0.5 A direct electric current inactivated lipase and protease producing extremely halophilic bacteria (10(5)-10(6) CFU/mL), which were grown separately in the liquid Brown media within 10 min. Voltage levels; 2.86-3.38 V did not change in all the brine solutions containing salt samples during electrical treatment, but the voltage levels in all the liquid Brown media containing both salt samples and protease-plus-lipase producing extremely halophilic bacteria decreased proportionally to the halobacterial population until the entire halobacterial population was inactivated. When the halobacterial population in the liquid Brown media was completely destroyed by the direct electric current, the voltage levels started to increase. This important clue might be used to predict inactivation time of all of the halobacterial populations grown in the brine solutions containing organic substances in the hide industry. It was also detected that the temperatures and pH values of the test media changed during the treatment. The maximum temperature rise was 9 degrees C and the pH increased by 5. These results showed that applying a 0.5 A direct current is a very effective method to kill extremely halophilic bacterial populations in salt used in hide preservation. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: low-level direct electric current; extremely halophilic bacteria; salt; hide industry; INACTIVATION; QUALITY; METABOLISM; SEAWATER; DAMAGE; MILK